Post COVID-19 Organizing Pneumonia: The Right Time to Interfere - Bieksiene, Kristina; Zaveckiene, Jurgita; Malakauskas, Kestutis; Vaguliene, Neringa; Zemaitis, Marius; Miliauskas, Skaidrius (Medicina (Kaunas, Lithuania), 2021)
The COVID-19 pandemic dramatically changed medical care. Healthcare professionals are faced with new issues. Patients who survived COVID-19 have plenty of different continuing symptoms, of which the most common are fatigue and breathlessness. It is not well known how to care for patients with persistent or worsening respiratory symptoms and changes on chest X-ray following COVID-19 pneumonia. In this article, we talk about a subgroup of patients with organizing pneumonia following COVID-19 pneumonia that could be effectively treated with systemic glucocorticoids. It is important that patients with COVID-19 pneumonia be followed-up at least three weeks after diagnosis, in order to recognize early lung damage. We are providing a management algorithm for early diagnosis of lung diseases after COVID-19 pneumonia.